Simplify expression - which expression is equivalent to:

3(m + 2) − 4(2m − 9)

Correct answer:

x = 42-5m

Step-by-step explanation:

x = 3(m + 2)  4(2m  9) x = 3m + 6  8m + 36 x=425m

Did you find an error or inaccuracy? Feel free to write us. Thank you!

Tips for related online calculators
Do you have a linear equation or system of equations and looking for its solution? Or do you have a quadratic equation?

You need to know the following knowledge to solve this word math problem:

Related math problems and questions: